Tinjauan Literatur: Pelanggaran Prinsip Dasar Etika Auditor di Indonesia - Vivy Yulianty; Indah Risti Anggraeni; Trinandari Prasetyo Nugrahanti (Journal of Innovative and Creativity, 2025)
This study discusses violations of the basic principles of auditor ethics in Indonesia that can reduce public trust in financial reports. The ethics of the auditor profession are very important, especially the five main principles in the accountant's code of ethics: integrity, objectivity, professional competence and prudence, confidentiality, and professional behavior. This study aims to identify the factors that cause violations of ethical principles, the impact of ethical violations and efforts to Implement and Strengthen Auditor Professional Ethics. This study uses a literature review method with the Systematic Literature Review (SLR) method by analyzing 13 Sinta indexed journals published in the last 5 years. The results of the study indicate that ethical violations often occur due to pressure from clients, weak supervision, and lack of understanding of ethical standards. It was found that the implementation of the code of ethics has not been fully effective in the field. Several cases show weak integrity and objectivity of auditors in dealing with conflicts of interest. This poses a risk to the credibility of the auditor profession. Therefore, the understanding and application of ethics need to be consistently improved. The recommendation of this study is the importance of ongoing training and strengthening regulations and supervision to prevent future violations.